PEMBERDAYAAN KADER DALAM PEMBUATAN OVITRAP SEDERHANA GUNA MENCEGAH PERKEMBANGBIAKAN JENTIK NYAMUK DI RW 01 DESA CEMANI - Salma Nabilah Fauziyyah; Putri Isha Fidhia Arofah; Lintang Ayuninggar; Nadya Umami Komalasari; Putri Adinda Cintia Bella; Widyaningsih Widyaningsih; Difka Fitra Naviri; Anggraeni Oktavia R; Berliandina Putri Permata V; Andiny Putri Pramudyta; Farizan Nur Raehan; Farros Arya Adhividyatama (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2026)
From January to mid-June 2025, 23 cases of dengue fever (DHF) were found in RW 01 Cemani Village, which is an increase in cases. The main problem partners face is the lack of understanding and skills among health workers for preventing DHF through simple, environment-based innovations. This activity aims to empower health cadres by providing education and training on making ovitraps as a tool for monitoring and controlling Aedes aegypti mosquito larvae. This activity is implemented in three stages: preparation, intervention, and evaluation. The preparation stage included licensing and preparing educational media and practical tools. The intervention stage involved delivering interactive materials, demonstrating ovitrap-making, and providing direct practice in making ovitraps using simple materials in groups. The evaluation stage involved observing ovitrap-making skills, cadre attendance, and pocket book usage independently. The results showed that ≥90% of the cadres attended, 85.7% could recreate ovitraps, and 95% used pocket books during practice. These resu lts prove that participatory training effectively improves cadres' skills and strengthens their capacity as agents of change in the community. In conclusion, the demonstrative method increased the cadres' knowledge and skills in independently making ovitraps. It is suggested that cadres continue.